Distinctive Rhetorical Models of Lexical and Grammatical Structure of The Uzbek Language - Abdullayeva Dilorom Akhmedovna (Genius Publishing Group, 2021)
The article provides general information about the lexical and grammatical structure of the Uzbek language. However, ideas about rhetorical speech models are also presented and analyzed using examples.
Keywords: Lexical and grammatical structure; rhetorical speech models; leading specialists; nominative function